Study of Utilization of Hydrological Services and Economic Value of Humboe Water Resources by Ermera Community - Martins, Leopoldino Vasco; Luis Pereira (International Journal of Integrative Sciences, 2024)
This study aims to determine the volume of water use of the community of Humboe Village, Ermera Municipality for household needs and to determine the economic value of hydrological environmental services in the Forest Area in Humboe Villag. This research was carried out in Ermera, taking place from January to March 2023. The variables observed in this study are the volume of water used for household needs, namely the need for clean water (m3/month), the economic value of water based on the price applicable to household needs (U$) and the willingness to pay (WTP) by the water user community (Rp. Sample determination is carried out by Simple Random Sampling, with the number of samples taken as much as 10% or 40 families out of a total of 140 household’s members of pipe-based management. The data collection method is carried out by taking secondary data and direct interviews with the public using structured questionnaires. The results of the study show that the average water volume over the past year in Humboe Village is 41.38541667 m3/year with 140 households using Humboe springs